The Effect of Contextual Teaching Learning (CTL) Model on Students’ Achievement in Elementary School - Arief Aulia Rahman; Zulkifli Zulkifli; Ilham Kamaruddin; Devi Syukri Azhari; Agus Supriyadi (research, training and philanthropy institution Natural Aceh, 2023)
This study aims to determine the effect of the CTL model on the learning outcomes of fifth-grade students at SD Negeri Peunaga Cut Ujong and to find out how much influence the CTL model has on the learning outcomes of fifth-grade students at SD Negeri Peunaga. Cut Ujong. The approach in this study uses a quantitative approach. This type of research uses a pre-experimental design. The population in this study were the fifth-grade students of SD Negeri Peunaga Cut Ujong, as many as 26 students. The sampling technique used in this research is intact-group comparison. The sample in this study was 13 students in the experimental class and as many as 13 students in the control class. The data collection techniques used in this study were observation, tests, and documentation. This study's instruments used to collect data consisted of observation sheets, test sheets, and validation sheets. The results of this study are from the analysis obtained tcount = 0.965 > ttable = 0.05, it is concluded that the hypothesis is accepted, the conclusion is that there is a difference or influence of the CTL model on student learning outcomes between students who are taught using the CTL with students who are taught by not using CTL model.